Cirques of the Presidential Range, New Hampshire, and surrounding alpine areas in the northeastern United States - Davis, P. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
Abstract Evidence for rejuvenation of cirque glaciers following wastage of continental ice remains elusive for the Presidential Range and Mount Moosilauke of New Hampshire, Mount Katahdin and the Longfellow Mountains of Maine, and the Adirondack Mountains of New York. At Ritterbush Pond in the northern Green Mountains of Vermont, radiocarbon ages from lake sediment cores suggest that a low-altitude valley head, located up- valley of a series of cross-valley moraines, was ice-free by 11,940 14 C yrs BP (Bierman et al. , 1997). Although some workers argue that these moraines in Vermont are evidence for cirque glaciation, the moraines could have been formed by a tongue of continental ice during deglaciation. At Johnson Hollow Brook valley in the Catskill Mountains of New York, a radiocarbon age from basal sediments in a pond dammed by a moraine suggests that glacier ice may have persisted until 10,860 14 C yrs BP (Lederer and Rodbell, 1998). Because this moraine appears to have been deposited by a cirque glacier, the radiocarbon age provides the best evidence in the northeastern United States for cirque glaciation post-dating recession of continental ice. Cirque morphometric data, compiled from newly available topographic maps, add to the conundrum that these two sites in the Green and Catskill Mountains should not be nearly as favorable for maintaining local glaciers post- dating icesheet recession as higher-altitude and better-developed cirques in the Presidential Range and Mount Katahdin, where evidence for post-icesheet cirque glaciers is lacking.